2020
DOI: 10.3390/antibiotics9030118
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Marine Microbial Communities Proximal to a Florida Sewage Outfall System

Abstract: Water samples were collected at several wastewater treatment plants in southeast Florida, and water and sediment samples were collected along and around one outfall pipe, as well as along several transects extending both north and south of the respective outfall outlet. Two sets of samples were collected to address potential seasonal differences, including 38 in the wet season (June 2018) and 42 in the dry season (March 2019). Samples were screened for the presence/absence of 15 select antibiotic resistance ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
(18 reference statements)
0
16
0
Order By: Relevance
“…The landlocked nations in the northern part of India account for about 30% of the world population, which could be sewage and industrial effluent [ 99 , 100 , 101 ]. Such anthropogenic activity enriches antibiotic-resistant genes in the coastal environment [ 102 , 103 , 104 ]. Furthermore, our previous metagenomic studies identified the prevalence of ARGs in the Kerala mangrove sediments [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…The landlocked nations in the northern part of India account for about 30% of the world population, which could be sewage and industrial effluent [ 99 , 100 , 101 ]. Such anthropogenic activity enriches antibiotic-resistant genes in the coastal environment [ 102 , 103 , 104 ]. Furthermore, our previous metagenomic studies identified the prevalence of ARGs in the Kerala mangrove sediments [ 105 ].…”
Section: Discussionmentioning
confidence: 99%
“…While ammonia was detected in both DWW (0.75) and HWW (0.13), nutrients such as nitrites and nitrates were not detected in HWW. Literature evidence suggests that the presence of antibiotic compounds in the environment is detrimental, as they may kill off nitrifying and denitrifying bacteria, impacting the process of nitrogen fixation in the terrestrial environment [ 33 ] while at the same time exerting a selective pressure that favors the proliferation of antibiotic-resistant bacterial communities [ 34 , 35 ]. The concentration of chloride and fluoride ions in HWW exceeded the EPA permissible limits as well as the Indian standards for wastewater discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Although no recognized pathogenic GNB species were identified, many culturable isolates exhibited resistance to clinically used antimicrobial agents. Most studies assessing the presence of drug resistance in environmental bacteria thoroughly characterize a small number of sites, typically near known point-source pollutant effluent locations [1,17,18,26,34,35]. There have also been some comparative surveys across multiple water bodies [6,15].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be related to secondary and tertiary treatment operations and control measures for all wastewaters that drain into the Bay [28], in combination with the large dilution factor due to tidal exchange, resulting in low ambient sediment bacterial pollution in this estuary. These hypotheses could be tested in the future by evaluating resistance profiles and mechanisms in bacteria obtained from point sources and adjacent locations, including wastewater discharge effluents [1,4,18,34,35]. However, our study represents just one line of evidence, and routine water monitoring does periodically detect elevated fecal coliforms at some beaches [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation